Optimization of The Use of LKPD in The Implementation of Problem Based Learning to Improve Students' Critical Thinking Abilities - rimadhani, vinda (J-SES : Journal of Science, Education and Studies, 2024)
This study aims to optimize the use of LKPD in implementing PBL to improve students' critical thinking skills. The research method is classroom action research (CAR). The focus of the research is on the class and the learning process in it, especially on critical thinking skills in working on LKPD which is measured through observation. The study uses the PBL (Problem Based Learning) model with descriptive data collection tools. The results of the study showed that at the first meeting, students' critical thinking skills only reached 65% with moderate criteria. However, over time and the second meeting there was an increase in students' critical thinking skills. In a study conducted in class VIII C of SMP Muhammadiyah 1 Surabaya, the results showed that the activities of teachers and students in implementing LKPD with the PBL model in science subjects had met good criteria. Students' critical thinking skills taught through the PBL model have been implemented in accordance with the steps set.